Retroreflection-based optical biosensing: From concept to applications - Han, Yong Duk; Kim, Ka Ram; Lee, Kyung Won; Yoon, Hyun C. (Biosensors and Bioelectronics, 2022)
Optical biochemical assays that utilize traditional optical signaling labels, such as fluorophores and fluorescent nanoparticles, have been extensively applied in the development of optical biosensors. However, traditional optical-label-based analytical approaches require expensive and sophisticated optical instruments; thus, the application of traditional optical-label-based biochemical assays to optical biosensors in point-of-care testing (POCT) concepts that require cost-effectiveness and user-friendliness remains challenging. Retroreflection-based optical biosensing technology that utilizes micro-sized retroreflectors as an optical signaling label is being studied as a promising technological alternative to overcome the drawbacks of conventional optical-label-based biosensors. Retroreflection is an optical phenomenon whereby light rays strike a specific surface, a retroreflector, and are redirected to the light source along the inverse direction of the incident light. Biosensors that involve the retroreflection principle and retroreflector-type optical label offer distinctive advantages, such as the cost-effective simplification of optical instrument configuration, highly flexible applicability to various biochemical assays, and high analytical capability; therefore, their further applications toward the biosensing platform for POCT is highly promising. This review introduces the fundamentals of retroreflection and summarizes recent research achievements of retroreflection-based optical biosensor development from the perspective of how retroreflectors can be coupled and utilized with the optical biosensing principle as optical signal labels. The expected future applications of retroreflection-based optical biosensor technology is also discussed.
Keywords: Bio-imaging; Biochemical assay; Immunosensing; Nucleic acid sensing; Optical bio-sensing; Optical bio-sensors; Optical labels; Optical signalling; Retro reflection; Retro-reflectors; Biosensing Techniques; Nanoparticles; Point-of-Care Testing; Bioimaging; Immunosensing; Nucleic acid sensing; Optical biosensor; Retroreflection